Comparative studies of two processing methods of bagoong alamang (acetes ep.) production. - Demegillo, Annie Rose (College of Fisheries, University of the Philippines, 1993)
Two traditional methods of "bagoong alamang" production, the wet fermentation method and the fermentation process which involves partially-drying of the raw material prior to salting and subsequent fermentation, were evaluated. Salt and water contents of the products were adjusted for the products to obtain the same water activity (Aw) values but different percent moisture content. Using the partially-dried fermentation method, the raw material was surface dried, a process which lasted for 2 hours and 20 min, upon which, the material obtained a 20% lost in weight. The development of odor and flavor of the products were evaluated and compared during the 12 week fermentation period. Changes in amino-N, ammonia-N and total volatile acids were determined and compared. The salt content, moisture content, and Aw of the products were likewise measured. Results reveal that the percent moisture content of wet fermented product (Product A) and the partially-dried fermented product (Product B) are 63.168% and 59.000%, respectively. However, the products obtained statistically the same Aw values. Product B obtained higher amino-N, ammonia-N, and total volatile acids values than Product A. The delay in salting in Product B due to sundrying allowed the proliferation of microorganisms and its resulting biochemical changes, thus resulting to this observed difference in values. The higher initial values of volatile acids and ammonia-N in Product B after 2 days of storage, 14.24 mg/g and 7.27 mg/100g, respectively, as compared to the final values of 11.53 mg/g total volatile acids and 5.93 mg/100g ammonia-N, indicate that the bulk of these compounds were formed in Product B even before salting. Likewise, the high amount of amino-N which gradually developed as fermentation advances could have also been formed even before salting. Product A and B's acceptability in terms of flavor show no statistical difference at p>0.05, although Product A possessed a freshly salted shrimp flavor while Product B exhibited a slight off flavor at the start of storage. On the other hand, flavor acceptability of both Products A and B increased during storage. Gradually, the detectable fresh shrimp flavor and slight off flavor of the products diminished while cheesy flavor got developed. With regards to the saltiness of both products, the panelists found the products with objectionable salty flavor. Odor of Product A has a higher acceptability than Product B, with the latter having observed ammoniacal odor which was found objectionable by the panelists. Although the at the start of storage, the products exhibited different characteristic odors, both products gradually developed the desired cheesy odor during storage; Product B developed such odor only during the last four weeks of storage. These implies then that the method of preparation of the shrimp paste product greatly affects odor development. The increasing acceptability in terms of odor and flavor during storage implies that both products remain acceptable even after three (3) months of storage.